China’s “Informationised Warfare”: Impact on the Region - Bitzinger, Richard A. (2016)
China’s People’s Liberation Army (PLA) has undertaken many significant reforms in recent months to better fight and win “informationised wars”. This is coupled with an aggressive behaviour driven by a sense of victimisation, as seen in Beijing’s posture over maritime territorial disputes. This invites offsetting actions on the part of the region.